The Role of Horseshoe Crabs in the Biomedical Industry and Recent Trends Impacting Species Sustainability - Krisfalusi-Gannon, Jordan; Ali, Waleed; Dellinger, Kristen; Robertson, Lee; Brady, Terry E.; Goddard, Melinda K. M.; Tinker-Kulberg, Rachel; Kepley, Christopher L.; Dellinger, Anthony L. (Frontiers in Marine Science, 2018)
Every year the Atlantic horseshoe crab (Limulus polyphemus) arrives on shore to spawn, a sight once taken for granted. However, in addition to the gradual climate changes impacting all ecosystems, commercial demand from the widespread application of Atlantic horseshoe crab blood in industrial endotoxin testing and steady use as eel and whelk bait has brought the future of this enduring species into question. In response, regulations have been adopted to enhance the traceability and record keeping of horseshoe crab harvest, which has historically been difficult to track. However, these regulations do not restrict or limit LAL harvest in any significant manner. Still, sometimes-lethal biomedical bleeding process and associated behavioral changes pose a risk to horseshoe crab viability after bleeding and once returned to the waters. As a result, regulators and environmentalists are concerned that current trends and overfishing of this marine arthropod will significantly impact the surrounding ecosystem. This review examines their role and recent trends in the biomedical industry that are impacting these ancient creatures and the derivative effect on shorebirds, while considering emerging alternatives where feasible, as well as ways to ensure sustainable and pragmatic harvesting strategies. Ultimately, healthy populations of horseshoe crabs are vital to restoring and maintaining ecosystems while balancing the need for medical and research applications entirely dependent on these unique creatures.